Pengaruh Agresivitas Pajak, Leverage, Profitabilitas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Yolanda, Vera; Widati, Listyorini Wahyu (Universitas Muhammadiyah Metro, 2024)
This research aims to test and analyze the influence of Tax Aggressiveness, Leverage, Profitability and Company Size on Company Value. The population of this research comes from food and beverage sector manufacturing companies listed on the IDX in 2020-2022. This research uses quantitative methods using secondary data obtained from financial reports. Which obtained 60 samples using the purposive sampling method from 80 companies. The data analysis method uses IBM SPSS 25 software. The results of this research show that only the profitability variable has an effect on company value.